Satisfaction, quality of life and perception of patients regarding burdens and benefits of vitamin K antagonists compared with direct oral anticoagulants in patients with nonvalvular atrial fibrillation. (June 2017) - Contreras Muruaga, Ma del Mar; Vivancos, José; Reig, Gemma; González, Ayoze; Cardona, Pere; Ramírez-Moreno, José Mª; Martí, Joan; Suárez Fernández, Carmen
Aim: To compare the satisfaction of patients treated with vitamin K antagonists (VKA) with that of patients treated with direct oral anticoagulants (DOACs) and to determine the impact on quality of life of both treatments in patients with nonvalvular atrial fibrillation (NVAF).Methods: Cross-sectional multicenter study in which outpatients with NVAF completed the ACTS (Anti-Clot Treatment Scale), SAT-Q (Satisfaction Questionnaire) and EQ-5D-3L (EuroQol 5 dimensions questionnaire, 3 level version) questionnaires.Results: The study population comprised 1337 patients, of whom 587 were taking DOACs and 750 VKAs. Compared with VKAs, DOACs were more commonly prescribed in patients with a history of stroke and in patients with a higher thromboembolic risk. The study scores were as follows: SAT-Q: 63.8 ± 17.8; EQ-5D-3L total score: 75.6 ± 20.9; visual analog scale: 63.1 ± 20.6; ACTS Burdens: 51.8 ± 8.4 and ACTS Benefits: 11.9 ± 2.4. The ACTS Burdens score and ACTS Benefits score were higher with DOACs than with VKAs (54.83 ± 6.11 vs 49.50 ± 9.15; p < 0.001 and 12.36 ± 2.34 vs 11.48 ± 2.46; p < 0.001 respectively).Conclusion: NVAF patients treated with oral anticoagulants had many comorbidities and a high thromboembolic risk. Satisfaction and quality of life with oral anticoagulants were high, although they were both better with DOACs than with VKAs.